Periods of prey absence and stability of the spider mite biological control - Oliveira, Hamilton; Duarte, Vanessa; Rezende, Daniela; Fadini, Marcos Antônio Matiello; Pallini, Angelo (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to access the biological parameters of the predator mite Phytoseiulus macropilis in the food absence for periods of one or more days. Data evaluated were: egg number per female per day; total number of eggs; longevity of females; and the offspring sex rate. Female in starvation for three or more days showed decrease in all biological variables. P. macropilis only will settle in the field if patch populations occupied by spider mite are not very distant from each other.